Potential Role of N-Cadherin in Diagnosis and Prognosis of Diabetic Nephropathy - Ali, Hamad; Abu-Farha, Mohamed; Hammad, Maha M.; Devarajan, Sriraman; Bahbahani, Yousif; Al-Khairi, Irina; Cherian, Preethi; Alsairafi, Zahra; Vijayan, Vidya; Al-Mulla, Fahd; Attar, Abdulnabi Al; Abubaker, Jehad (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is a serious complication of diabetes affecting about half the people with diabetes and the leading cause of end stage renal disease (ESRD). Albuminuria and creatinine levels are currently the classic markers for the diagnosis of DN. However, many shortcomings are arising from the use of these markers mainly because they are not specific to DN and their levels are altered by multiple non-pathological factors. Therefore, the aim of this study is to identify better markers for the accurate and early diagnosis of DN. The study was performed on 159 subjects including 42 control subjects, 50 T2D without DN and 67 T2D subjects with DN. Our data show that circulating N-cadherin levels are significantly higher in the diabetic patients who are diagnosed with DN (842.6 ±98.6 mg/l) compared to the diabetic patients who do not have DN (470.8 ±111.5 mg/l) and the non-diabetic control group (412.6 ±41.8 mg/l). We also report that this increase occurs early during the developmental stages of the disease since N-cadherin levels are significantly elevated in the microalbuminuric patients when compared to the healthy control group. In addition, we show a significant correlation between N-cadherin levels and renal markers including creatinine (in serum and urine), urea and eGFR in all the diabetic patients. In conclusion, our study presents N-cadherin as a novel marker for diabetic nephropathy that can be used as a valuable prognostic and diagnostic tool to slow down or even inhibit ESRD.